ALL WORK AND NO PLAY MAKES JACK A DULL BOY: THE SLOGAN FOR A SPARKLING TODAY - Gitey, Mehnaz Nuruddin (Journal of Pakistan Psychiatric Society, 2023)
Living in an era of “Parhoge lihoge banoge nawab, kheloge kudoge tau hogay khrab”(Literacy make a person a leader while sports spoils a person)it is learnt with experience that sports spoils a person’s comfort zone, opens a person up to challenges, challenging a person to meet them. A person engaged in sports is not only physically healthy but is mentally sound too. Sports mentally engage a person into positivity, distracting all physically active competitors away from conflict and negativity.